Evaluasi Air dan Oli sebagai Material Dasar Phantom Anechoic untuk Aplikasi Ultrasonography (USG) - Maulani Qonitin,; Harsoyo, Imam Tri; Yugiantoro, Darojat; Ibad, Asyrofil (JFT: Jurnal Fisika dan Terapannya, 2025)
The increasing demand for ultrasonography (USG) phantoms for training and equipment calibration highlights the need for effective and affordable local alternatives. This study investigates two base materials water and oilas anechoic phantom media through a laboratory-based experimental approach. Phantoms were constructed by placing two test objects a gasoline filled straw and a piece of Styrofoam into separate containers filled with each medium, then scanned using the Mindray DP-10 ultrasound device. Measurements of object diameter and depth were conducted five times to assess precision and image quality. Numerical data and visual outputs were analyzed comparatively to evaluate acoustic characteristics, image clarity, noise level, and stability. The findings reveal notable differences in imaging performance between the two materials, reflecting the influence of acoustic impedance and viscosity on phantom effectiveness in USG applications.